Prevalence of Toxoplasma Gondii in Broiler Referred to Kashan Industrial Abattoir, Central Iran, 2023 - Erfan Amiri; Hossein Hooshyar; Hossein Nazemorraaya; Mohammadreza Shiee; Sima Rasti; Gholam Abbass Moosavi (Tehran University of Medical Sciences, 2023)
Background and Aim: Toxoplasma gondii is one of the important food-borne parasitic pathogens that infect humans and a wide range of warm-blooded animals. Consumption of poultry meat, especially chicken, is a potential risk of transmission of toxoplasmosis to humans. This study aimed to determine the prevalence of T. gondii infection in industrial broilers referred to the Kashan poultry abattoir, Iran, in 2023. Materials and Methods: This cross-sectional study was performed on 114 brain and heart samples of industrial broilers were randomly collected from Kashan poultry abattoir. Two prepared direct smears from each sample were stained with Giemsa stain and examined microscopically for the presence of tissue cysts of T. gondii. The genomic DNA was extracted using a commercial kit. PCR method was used for detection of the B1 genome of T. gondii using specific primers. The PCR product was evaluated by electrophoresis on a 1.5% agarose gel. The results were analyzed with descriptive statistics using SPSS software. Results: Of 114 chicken samples, 65 (57%) and 49 (43%), were male and female respectively. Totally, 12 samples (10.5%) were positive for T. gondii infection. T. gondii DNA fragments were detected in 8 (7.06%) of the samples. Microscopy examination revealed T.gondii in 6 (5.26%) samples. All infections were related to brain samples, and no infection was detected in heart muscle samples. Conclusion: Infection with T. gondii is considerable in broilers in the Kashan region. Therefore, preventive measures such as training people to properly cook meat before consumption and avoiding eating raw or under‑cooked poultry meat products are recommended to prevent human infection to T. gondii. In order to stop life cycle of this parasite, avoiding using raw bird meat for feeding pets such as cats is recommended.